From behaviour to design: implications for artifact ecologies as shared spaces for design activities - Vasiliou, Christina; Ioannou, Andri; Zaphiris, Panayiotis (My University, 2019)
Researchers are increasingly exploring collaborative behaviour in complex socio-technical systems through in-the-wild investigations to understand, evaluate and technology. The space configuration and tools available in such activities are crucial for the successful collaboration of a group. This work offers an in-the-wild examination of six groups tackling a design project working in an artifact ecology, a space rich in physical and digital artifacts. We delve into the physical and digital space of each of the groups during a 3-month duration to obtain a rich understanding of their collaborative activities. The aim of this work is two-fold; provide summative narrations of each one of the five models of DiCoT to extract design implications and evaluate the usefulness of DiCoT as an analytical tool for understanding artifact ecologies. Through a rich dataset–interviews, focus groups, reflective diaries, online interactions, and video recordings–we construct a summative description of the group behaviour based on the methodological framework of Distributed Cognition for Teamwork. Drawing on these narrations, we provide design implications on the use of an artifact ecology as a shared space for design activities. Both outcomes are then used to evaluate the usefulness of DiCoT as an analytical tool for artifact implications.
Keywords: Artifact ecology; CSCW; Distributed cognition; Shared spaces